Strategi Pemasaran dalam Meningkatkan Daya Saing UMKM Nasi Tumpeng Rajabasa Bandar Lampung - Melia Utami; Riswan Riswan (Jurnal Ilmu Administrasi Bisnis, 2023)
Environmental factors, both internal and external, often become obstacles to the growth of MSMEs. Ignorance for MSME actors to anticipate environmental changes, and not having a marketing strategy has resulted in MSME actors lacking competitiveness in the products offered. SWOT analysis is an alternative in helping MSMEs determine marketing strategies and anticipate changes in the business environment. The purpose of this research is to find out the right strategy for increasing sales in the Nasi Tumpeng Rajabasa culinary business using qualitative methods with primary data sources and using SWOT analysis which consists of Strengths, Weaknesses, both of which are internal factors, and Opportunities. Opportunities), Threats (Threats) which are part of external factors. Given the data analysis carried out, it was concluded that Tumpeng Rajabasa can improve the quality of its products by providing many interesting menus, as well as maximizing customer service for its products. In addition, the practicality offered by catering services is very profitable for MSME actors, so that UMKM Tumpeng Rajabasa can reduce the total cost of the price of production staples, and guarantee the best quality as a competitive advantage strategy.Faktor lingkungan baik dari internal ataupun eksternal sering kali jadi penghambat bagi pertumbuhan UMKM. Ketidaktahuan bagi para pelaku UMKM untuk mengantisipasi pergantian lingkungan, dan tidak punya strategi pemasaran mengakibatkan pelaku UMKM kurang punya daya saing pada produk yang ditawarkan. Analisis SWOT jadi alternatif dalam membantu para UMKM menetapkan strategi pemasaran dan mengantisipasi pergantian dari lingkungan bisnis tersebut. Tujuan riset ini ialah agar diketahui strategi yang tepat dalam menaikkan penjualan pada usaha kuliner Nasi Tumpeng Rajabasa memakai metode kualitatif dengan sumber data primer serta memakai analisis SWOT yang terdiri atas Strength (Kekuatan), Weakness (Kelemahan), keduanya ialah faktor internal, dan Opportunities (Peluang), Threats (Ancaman) yang jadi bagian dari faktor eksternal. Mengingat analisis data yang dilaksanakan, didapat kesimpulan jika Tumpeng Rajabasa dapat menaikkan mutu produknya dengan menyediakan banyak menu yang menarik, juga memaksimalkan pelayanan pada pelanggan pada produknya. Ditambah kepraktisan yang ditawarkan dengan jasa catering sangatlah menguntungkan pelaku UMKM, hingganya UMKM Tumpeng Rajabasa dapat menekan total biaya dari harga bahan pokok produksi, serta menjamin mutu yang terbaik jadi strategi keunggulan bersaing.